Website sebagai Sarana Promosi Perpustakaan di SMA N 1 Jogjakarta - Nisa-Un Naja (UPT Perpustakaan UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2020)
This study aims to determine the extent to which the website is used in library promotion efforts. The method used in this research is descriptive quantitative. Data collection techniques using interviews, observation, documentation and through a questionnaire. The results of the study showed that the website as a promotional tool in the library of SMA N 1 Jogjakarta was categorized well with an average value of 3.5. The researchers obtained these results through 11 indicators divided by 7 indicators from the theory of effectiveness and 4 indicators from promotion. First, production with an average value of 3.65. Second, quality with an average of 3.67. Third, efficiency with an average of 3.58. The fourth is satisfaction with an average score of 3.59. Fifth competition with an average of 3.51. The six developments with an average of 3.42. The seven continued with a mean of 3.71. The eighth is through library promotion indicators, which can introduce library functions with an average of 3.53. Ninth, increasing reading interest by an average of 3.46. Ten, namely introducing library services and services with an average value of 3.53. Eleventh, developing understanding of the library with an average value of 3.49. Abstrak Penelitian ini bertujuan untuk mengetahui sejauh mana penggunaan website dalam upaya promosi perpustakaan. Metode yang digunakan dalam penelitian ini yaitu deskriptif kuantitatif. Teknik pengumpulan data menggunakan interview, observasi, dokumentasi serta melalui angket. Adapun hasil penelitian menunjukan bahwa website sebagai sarana promosi di perpustakaan SMA N 1 Jogjakarta dikategorikan baik dengan nilai rata-rata 3,5. Hasil tersebut peneliti peroleh melalui 11 indikator dengan pembagian 7 indikator dari teori efektivitas dan 4 indikator dari promosi. Pertama, produksi dengan nilai rata-rata 3,65. Kedua, mutu dengan rata-rata 3,67. Ketiga, efisiensi dengan rata-rata 3,58. Keempat kepuasan dengan nilai rata-rata 3,59. Kelima persaingan dengan rata-rata 3,51. Keenam pengembangan dengan rata-rata 3,42. Ketujuh kelangsungan dengan rata-rata 3,71. Kedelapan yaitu melalui indikator promosi perpustakaan yakni dapat mengenalkan fungsi perpustakaan dengan rata-rata 3,53. Kesembilan, meningkatkan minat baca dengan rata-rata 3,46. Sepuluh yaitu mengenalkan jasa dan layanan perpustakaan dengan nilai rata-rata 3,53. Kesebelas, mengembangkan pengertian perpustakaan dengan nilai rata-rata 3,49.